AUDIT QUALITY CONTROL: METHODS OF EXTERNAL QUALITY CONTROL OF AUDIT WORK - Sarsengali Xalmuratovich, Bayjanov; Sarbinaz Turdimuratovna, Utegenova (IJBLE Scientific Publications Community Inc., 2021)
The article states that audit of financial statements is a necessary and important tool for the economy development, the results of external quality control of audit work in audit companies shows that timeliness and necessity of making these decisions depend on the quality of audits. The existing theories of classification of subjects of audit quality control show that 3 parts: government (financial ministry), audit public associations and audit companies must work together, also time by time they should do external quality control of audit work. In this regard, it is necessary to consider the nature of audit quality control and those interested in the quality of audits.